2016
DOI: 10.1111/desc.12490
|View full text |Cite
|
Sign up to set email alerts
|

Attention allocation towards own face is pronounced during middle adolescence: an eye‐tracking study

Abstract: Increased interest in the self has long been deemed to be one of the most peculiar characteristics of adolescence. On the basis of this, we conjectured that attentiveness towards self-relevant information, especially one's own face, becomes more pronounced during the middle adolescence. The present study tested this hypothesis by comparing the pattern of visuospatial attention allocation to their own face among early, middle and late adolescent males using an eye-tracking methodology. The results have shown a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…There are several explanations for this null result. First, our previous study (Doi and Shinohara, 2018) has shown that male young Japanese do not show clear attentional prioritization of self face over other’s face after mid-adolescence. Taking into consideration the previous finding indicating that developmental change of face processing continues into late adulthood (Anastasi and Rhodes, 2005; Boutet et al, 2015), we might get a different picture if, we recruit younger or older population.…”
Section: Discussionmentioning
confidence: 94%
“…There are several explanations for this null result. First, our previous study (Doi and Shinohara, 2018) has shown that male young Japanese do not show clear attentional prioritization of self face over other’s face after mid-adolescence. Taking into consideration the previous finding indicating that developmental change of face processing continues into late adulthood (Anastasi and Rhodes, 2005; Boutet et al, 2015), we might get a different picture if, we recruit younger or older population.…”
Section: Discussionmentioning
confidence: 94%
“…Although we created three conditions and randomized (with some constraints) the positions of the distractors and the order in which we presented the matrices in our experiment, many other stimuli and procedures could have been used. Using an eye-tracking system does not preclude displaying two items [54], three items [55], or even five or more items. Thus, further studies are needed to ensure our findings concern recognition in general and are not specific to the format of our stimuli.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…With respect to social integration, adolescents detach from their parents and are more susceptible to peer influence (Parker et al., 2006) and the potential experience of rejection, exclusion, or bullying in school (Carlyle & Steinman, 2007; Juvonen & Gross, 2008; Pontes, Ayres, Lewandowski, & Pontes, 2018). Regarding self-esteem, adolescents show an increased self-consciousness and self-conflict (Doi & Shinohara, 2018; Parker et al., 2006), and self-esteem is considerably lower during this stage of life than in later life (Morin et al., 2017; Morin, Maiano, Marsh, Nagengast, & Janosz, 2013; Orth & Robins, 2014; Sanchez-Queija, Oliva, & Parra, 2017). With respect to well-being, studies show the emergence of diverse mental and physical problems in adolescence (Collishaw, 2015; Kessler et al., 2005; Merikangas et al., 2010).…”
Section: Introductionmentioning
confidence: 99%